2021
DOI: 10.1007/978-3-030-71995-1_20
|View full text |Cite
|
Sign up to set email alerts
|

Certifying Inexpressibility

Abstract: Different classes of automata on infinite words have different expressive power. Deciding whether a given language $$L \subseteq \varSigma ^\omega $$ L ⊆ Σ ω can be expressed by an automaton of a desired class can be reduced to deciding a game between Prover and Refuter: in each turn of the game, Refuter provides a letter in $$\varS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Our setting considers automata on finite words, and it focuses on the number of states required for recognizing a regular language. In [12], we used a similar methodology for refuting the recognizability of ω-regular languages by automata with limited expressive power. For example, deterministic Büchi automata (DBAs) are less expressive than their non-deterministic counterpart, and a DBA-refuter generates certificates that a given language cannot be recognized by a DBA.…”
Section: Discussion and Directions For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Our setting considers automata on finite words, and it focuses on the number of states required for recognizing a regular language. In [12], we used a similar methodology for refuting the recognizability of ω-regular languages by automata with limited expressive power. For example, deterministic Büchi automata (DBAs) are less expressive than their non-deterministic counterpart, and a DBA-refuter generates certificates that a given language cannot be recognized by a DBA.…”
Section: Discussion and Directions For Future Researchmentioning
confidence: 99%
“…For example, deterministic Büchi automata (DBAs) are less expressive than their non-deterministic counterpart, and a DBA-refuter generates certificates that a given language cannot be recognized by a DBA. Thus, the setting in [12] is of automata on infinite words, and it focuses on expressive power.…”
Section: Discussion and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Proving that NBWs are strictly more expressive than DBWs, Landweber showed that the language L 1 = (0 + 1) * • 1 ω (only finitely many 0's) is in NBW\DBW. The proof is simple and can be stated in a few lines or using a two-state expressiveness refuter (Kupferman and Sickert, 2021). Much harder is the proof that NRTs are strictly more expressive than NBTs.…”
Section: Introductionmentioning
confidence: 99%